Developing an equivalent toxicity area approach to comparing toxicity of urban road deposited sediments. (February 2020) - Zhan, Yuting; Yang, Bo; Hong, Nian; Guan, Yingjie; Liu, An; Du, Ye; Wu, Qianyuan; Guan, Yuntao
Abstract: Urban road stormwater has been seen as an alternative water resource for mitigating water scarcity. Road deposited sediments (RDS) is the primary source of road stormwater pollution since many toxic pollutants are attached to RDS and eventually enter stormwater runoff when rainfall events occur. This could threaten road stormwater reuse safety. This study developed an innovative equivalent toxicity area (ETA) approach to comparing overall toxicity of RDS among different road sites. In the ETA approach, the road surface area was used to represent how toxic the RDS generated from the area was. This ETA approach overcomes the difficulty to compare RDS toxicity among road sites due to variability of sampling volumes, which constrains the effective application of conventional toxicity comparison method of using pollutant amounts (loads/concentrations). Twelve road sites in Shenzhen, China were selected as a case study, where the ETA approach developed was used to compare their RDS toxicity using Chinese Hamster Ovary cells. Additionally, the key factors influencing RDS toxicity were identified by using a forward stepwise regression method. These outcomes provide a useful approach to comparing overall toxicity where various pollutant types with different amounts (loads/concentrations) and toxicity levels are present. Additionally, the results can also contribute to ensuring safety of RDS polluted stormwater reuse. Graphical abstract: Image 1 Highlights: An equivalent toxicity area (ETA) approach was developed to compare RDS toxicity. ETA overcomes issue to compare RDS toxicity due to variation of sampling volumes. Factors affecting RDS toxicity are land use > metal > traffic > surface condition > TS/TOC. Inadequacy of conventionally using solids to represent RDS pollution was confirmed. Abstract : An innovative equivalent toxicity area approach was developed to compare overall toxicity of RDS among different road sites.